2008
DOI: 10.1007/s11356-008-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate and land-use changes affecting river sediment and brown trout in alpine countries—a review

Abstract: Background, aim, and scope Catch decline of freshwater fish has been recorded in several countries. Among the possible causes, habitat change is discussed. This article focuses on potentially increased levels of fine sediments going to rivers and their effects on gravel-spawning brown trout. Indications of increased erosion rates are evident from land-use change in agriculture, changes in forest management practices, and from climate change. The latter induces an increase in air and river water temperatures, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 77 publications
1
47
0
2
Order By: Relevance
“…Generally, the combined effects of climate and changing land use have been predicted to increase future soil erosion in Alpine regions (Frei et al 2007). A rising snowline, intensified precipitation during the winter and strong leaching effects with no or sparse vegetation cover in late autumn and early spring could result in an increase in erosion especially in the Northern (mainly North-Western) Alps (Fuhrer et al 2006;Scheurer et al 2009). However, other models predict increased erosion susceptibility more on the southern part of the Alps (Bosco et al 2009).…”
Section: Soil Sediment Budgets Indicate Unsustainable Managementmentioning
confidence: 99%
“…Generally, the combined effects of climate and changing land use have been predicted to increase future soil erosion in Alpine regions (Frei et al 2007). A rising snowline, intensified precipitation during the winter and strong leaching effects with no or sparse vegetation cover in late autumn and early spring could result in an increase in erosion especially in the Northern (mainly North-Western) Alps (Fuhrer et al 2006;Scheurer et al 2009). However, other models predict increased erosion susceptibility more on the southern part of the Alps (Bosco et al 2009).…”
Section: Soil Sediment Budgets Indicate Unsustainable Managementmentioning
confidence: 99%
“…Long-term average annual discharge will not change significantly. Consequences of these changes of the Danube river flow regime due to climate change may include disruption of spawning, with decreased reproduction and recruitment, decreased oxygen concentrations in the summer and alteration of floodplain vegetation, decreases in young fish and other effects of decreased duration of floodplain inundation (Scheurer et al, 2009;Poff and Zimmerman, 2010).…”
Section: Model Validity and Climate Change Impacts For Selected Rivermentioning
confidence: 99%
“…Kundczewicz et al (2007) reviewed some publications that deal with the impacts of climate change induced river flow alterations on freshwater ecosystems, discussing decreased habitat availability due to decreased ice-jam flooding, impacts of lower water column depth on spawning of salmon, and impacts of reduced runoff on breeding grounds for water birds. In a review on the impact of climate and land use change on Alpine brown trout, Scheurer et al (2009) concluded that climate change induced increases of river discharge and sediment loads in winter and early spring could be especially harmful for brown trout reproduction and development of young life stages. Erwin (2009) reflected on the challenges to wetland conservation and restoration under climate change, pointing out the need to reduce non-climate stressors, including monitoring, in particular of invasive species that are favored by climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Studies for the Alps, pre-Alps and the hilly regions of the Swiss Plateau are rare. This includes small rivers, which are habitats for gravel spawning fish (Scheurer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The results of those empirical studies of fine sediment infiltration rates are difficult to generalize mostly due to different measurement methodologies (Sear et al, 2008). Hence, there is a need to compare methodologies as well as data on sediment input and riverbed clogging to achieve a better comparability of results from different studies and to increase knowledge on the interaction between fine sediment dynamics and fine sediment infiltration and accumulation (Scheurer et al, 2009). The aim of this study was to (i) compare results obtained by different methods used to capture temporal and spatial dynamics of suspended sediment and fine sediment infiltration and accumulation, (ii) test their suitability for a river in the Swiss Plateau, (iii) compare the results with hydrological data, and (iv) compare the results with literature data.…”
Section: Introductionmentioning
confidence: 99%